Investigation of Avian Reovirus Evolution and Cross-Species Transmission in Turkey Hosts by Segment-Based Temporal Analysis - Cheng-Shun Hsueh; Michael Zeller; Amro Hashish; Olufemi Fasina; Pablo Piñeyro; Ganwu Li; Jianqiang Zhang; Mohamed El-Gazzar; Yuko Sato (Viruses)
Avian reovirus (ARV) has emerged as an important pathogen in turkeys, causing economic losses through tenosynovitis, necrotizing hepatitis, immunosuppression, and enteric disease. Despite its ubiquity, the evolutionary history of ARV cross-species transmission among chickens, turkeys, and wild birds remains poorly understood, hindering effective control and surveillance. This study investigates ARV temporal phylogenetics with an emphasis on interspecies transmission in turkeys. Whole genome sequences (WGSs) from seventy-seven turkey cases and one quail case at the Iowa State University Veterinary Diagnostic Laboratory, along with 74–136 segment sequences per gene from GenBank (1970–2023), were analyzed. Temporal phylogenetic analyses identified chickens as the ancestral host, with spillover into turkeys beginning in the mid-20th century, followed by stable transmission within turkey populations. Migration analyses revealed predominantly unidirectional transmission from chickens to turkeys. WGS analyses showed high variability in the M2 and σC-encoding region of the S1 segment, suggesting selective pressure on outer capsid proteins. M2, S1 σC, and L3 had the highest substitution rates, implicating their role in adaptation and antigenic diversity. These findings highlight the complexity of ARV evolution across hosts and underscore the need for robust genotyping schemes and surveillance strategies to mitigate outbreaks in poultry.